Improving mathematics learning outcomes on subtraction material using canva-based learning media for grade 1 elementary school students - Novitasari, Yuliana; Deviana, Tyas; Widuri, Arisita (Universitas Nusantara PGRI Kediri, 2024)
The aim of this research is to improve the learning outcomes of grade 1 students in mathematics subtraction material at SDN 1 Kepatihan Tulungagung which consists of 21 students. The research method uses classroom action research which uses the spiral model emphasized by David Hopkins, where there are four stages, namely planning, action, observation and reflection (Hopkins, 2011: 91). The data collection techniques used were, 1) Observation, 2) Test, 3) Documentation, 4) Interview, then quantitative descriptive analysis was carried out from the data obtained with the following results: 1) At the pre-cycle stage the class average value was 73, 8 with a classical completion percentage of 38.09%. 2) Then, in the first cycle stage, the average class score increased to 81.47 with a classical completeness percentage of 42.85%. 3) Furthermore, in the second cycle stage the class average increased to 91.8 with a classical completeness percentage of 85.71%. Based on the results of the research conducted, it can be concluded that the use of Canva-based learning media can improve mathematics learning outcomes in subtraction material for grade 1 students at SDN 1 Kepatihan Tulungagung.